The role of smartphone applications as English learning tool among Chinese university students - Liu, Mengjie; Noordin, Nooreen; Ismail, Lilliati; Abd Rahim, Nur Aira; Zaremohzzabieh, Zeinab (Ninety Nine Publication, 2021)
This study aims to explore the impact of smartphone applications on Chinese non-English majors’ out-of-class English listening learning. The qualitative research method was adopted in this study. Four partic ipants who attended the semi-structured interviews and five online diaries were selected to provide data for the research. The results demonstrate that the utilization of smartphone apps can indeed have a positive influence on Chinese non-English majors' out-of-class English listening learning, and change their listening learning styles to a great extent. Fragmented learning time and informal learn ing place were widely accepted by students due to the flexib ility and portability of smartphone apps, which create more learning opportunities for them and in turn lengthens their learning time. Rich, authentic, high -quality, and up- to-date listening materials, English proficiency tests, and the function of recommendation offered by smartphone apps all provide a great convenience for students. However, this technology is not yet mature and can be further developed by ameliorating some negative factors, such as interference from other functions and applications of smartphones, small screens and reflected light, and lack of guidance and feedback.